Public Perceptions of Police in Fiji - Chand, Anand (Journal of contemporary criminal justice, 2022)
Members of the public may have positive, negative, or mixed perceptions of police. Previous research has demonstrated that public perceptions are shaped by their experiences and interactions with police and can influence trust, perceived legitimacy, and future cooperation. Limited research has examined public perceptions of police in small island developing states. This article explores public perceptions of police in Fiji, an island state in the Pacific region. This study employed a mixed-method approach based on qualitative interviews (n = 21) and quantitative surveys (n = 150). The findings show that only a minority of the participants had a favorable view of police, while the majority had a negative perception. The results reveal that police corruption and brutality are two significant concerns of the public that the Fiji Police Force will need to address to gain public respect, trust, confidence, and legitimacy.